RISIKO KREDIT SEBAGAI PEMODERASI PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Hari Raharja, Komang Adik; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2016)
This research is aimed to determine the effect of leverage and firm size on firm value and credit risk in moderating the effect of leverage and firm size on firm value. 27 banking companies is taken as sample on this research, by using purposive sampling method. Data is collected through non participant observation. This research uses multiple regression analysis and moderated regression analysis. Based on the results of analysis, found that leverage has a negative effect on firm value. Firm size has a positive effect on firm value. Credit risk able to weaken the negative effect of leverage on firm value. Credit risk is not able to moderate the effect of firm size on firm value.
Keywords: firm value, leverage, firm size, credit risk